Is there an Environmental Kuznets Curve for SO2 emissions? A semi-parametric panel data analysis for China. (February 2016) - Wang, Yuan; Han, Rong; Kubota, Jumpei
Abstract: The present study concentrates on a Chinese context and attempts to explicitly examine the impacts of economic growth and urbanization on sulfur dioxide emissions through investigation of the existence of an environmental Kuznets curve. Within the Stochastic Impacts by Regression on Population, Affluence and Technology framework, this is the first study to simultaneously explore the income/urbanization and sulfur dioxide emissions nexus, using panel data together with semi-parametric panel fixed effects regression. Our dataset is referred to a provincial panel of China spanning the period 1990–2012. With this information, we find evidence in support of an inverted U-shaped curve relationship between economic growth and sulfur dioxide emissions, but little evidence supporting a similar inference for urbanization and those emissions. Existence of the income–sulfur dioxide emissions environmental Kuznets curve implies that the economic growth vs. sulfur dioxide emissions dilemma can be resolved while income continues to increase. Also, these findings contribute to advancing the emerging literature on the development-pollution nexus.